Respuesta :
Focus on the first equation. The ordered pair (-4,12) means that x = -4 and y = 12. Keep in mind that x always comes first. Think alphabetical order.
What we do is simply replace every x with -4 and replace every y with 12. Let's see what happens
2x+y = 5
2*x+y = 5
2*(-4) + 12 = 5
-8 + 12 = 5
4 = 5
The last equation, 4 = 5, is FALSE. So because we have a false equation, it means that 2x+y = 5 is also false when (x,y) = (-4,12)
There is no way that (-4,12) is the solution to this system. It fails to satisfy the first equation.
What we do is simply replace every x with -4 and replace every y with 12. Let's see what happens
2x+y = 5
2*x+y = 5
2*(-4) + 12 = 5
-8 + 12 = 5
4 = 5
The last equation, 4 = 5, is FALSE. So because we have a false equation, it means that 2x+y = 5 is also false when (x,y) = (-4,12)
There is no way that (-4,12) is the solution to this system. It fails to satisfy the first equation.
Equation 1) 2x + y = 5
Equation 2) -5x - 2y = -6
We're trying to elminate (y) so that we could get (x) by itself, so to do so, we have to multiply ALL of equation 1 by 2, so that both equations have (2y) in them.
Equation 1) 2(2x + y = 5)
Equation 1) 4x+2y=10
Equation 2) -5x-2y=-6
Add equations together.
-x=4
x=-4
Plug in (x) into equation 1.
2(-4)-2y=-6
Simplify.
-8-2y=-6
Add 8 to both sides.
-2y=2
Divide both sides by -2.
y=1
(-4, 1)
So, (-4, 12) is NOT the correct answer.
~Hope I helped!~
Equation 2) -5x - 2y = -6
We're trying to elminate (y) so that we could get (x) by itself, so to do so, we have to multiply ALL of equation 1 by 2, so that both equations have (2y) in them.
Equation 1) 2(2x + y = 5)
Equation 1) 4x+2y=10
Equation 2) -5x-2y=-6
Add equations together.
-x=4
x=-4
Plug in (x) into equation 1.
2(-4)-2y=-6
Simplify.
-8-2y=-6
Add 8 to both sides.
-2y=2
Divide both sides by -2.
y=1
(-4, 1)
So, (-4, 12) is NOT the correct answer.
~Hope I helped!~